Pathways to materiality - Rogers, Jean,Serafeim, George (Harvard Business School, 2019)
Management and disclosure of environmental, social and governance (ESG) issues have received substantial interest over the last decade. In this paper, we outline a framework of how ESG issues become financially material, affecting corporate profitability and valuation. We argue that understanding this process is important both for actors driven by financial or societal motives. The former group, which includes companies and return-first investors, can use the framework to make resource allocation decisions based on expectations about future materiality thereby enhancing risk-adjusted returns. The latter group, which includes regulators, NGOs, and impact-first investors, can use the framework to design and implement interventions that create market-based incentives for companies and investors to align their behavior with social and environmental outcomes
10.2139/ssrn.3482546
Keywords: Graue Literatur; sustainability disclosure; ESG; materiality; social impact; corporate valuation